Factors Influencing Street Vendors’ Income in Campus Microeconomic Ecosystem - Lenda Lumentah (SOSIOEDUKASI, 2025)
Crucial questions, which have been lacking in the literature, particularly regarding informal microeconomies in suburban areas, were addressed in this research. Street food vendors in campus ecosystems play an important role in supplying food to the community and creating informal jobs; however, their income security is poorly reported in Eastern Indonesia. Primary data were gathered from 20 vendors between January and March 2025 using mixed methods. Vendors were classified into three spatial zones according to the shop's proximity to the campus, and income patterns were studied across academic cycles and digital adoption status. Results: Daily net income ranged between IDR 30,000 and IDR 85,000, and vendors in Zone A (close to the campus gate) earned much more than vendors in the peripheral zones. We found high income sensitivity to the academic calendar, with a decrease in income of 56% during semester breaks and an increase of 18% at the beginning of the new semester. Digital platforms were used by only five vendors (for example, GoFood), but they had a 47% higher daily income despite the commission costs. Barriers to adoption include limited digital literacy, smartphone access, and age. Volatility affected the food supply chain, and vendors used informal coping mechanisms to deal with the stress, such as operating hours, selling on local markets, or using savings, which were not sustainable for the long term. ​The results show that spatial access, institutional rhythms, technological divides, and social capital structurally determine vendor income. Resilience is seen as existing, but limited by systems of exclusion. The study concludes that inclusive urban and campus policies, such as equitable vendor areas, digital literacy training, vendor cooperatives, and social protection policies, are needed to integrate informal actors into sustainable local development systems